Productivity and Financial Analysis of Fishing Effort with Handline at Kutaraja Ocean Fishing Port Aceh Province - Manalu, Angga Setia; Zain, Jonny; Brown, Arthur (Journal of Coastal and Ocean Sciences, 2023)
Production of catches on hand line-fishing gear at Kutaraja Ocean Fishing Port has decreased, this is clearly seen from the level of fish production produced, which was 2.407.580 tons in 2018 compared to production in 2019, which was 2,285,750 tons. The fishing business, which has become one of the livelihoods of the Indonesian people, is a little riskier compared to other businesses because the fish which are the main target of this business is always moving dynamically. The research objectives were to determine productivity per GT, Trip, and ABK on hand line-fishing gear and to determine the financial feasibility analysis of fishing effort on hand line-fishing gear at Kutaraja Ocean Fishing Port. The benefits of this research are to increase knowledge and insight regarding productivity and financial analysis of the fishing line effort. The method used in this study is a survey method. The data analysis method used in this research is a descriptive analysis method. The results showed that the value of productivity per trip with large-size ships has a high amount of production compared to smaller ship sizes. This is because a larger ship has a carrying capacity or more carrying capacity. Hand line fishing with a vessel size > 30 GT has a relatively long payback period, i.e. < 5 years. While ships with a size of 5 GT. 6 GTs. 9 GTs. 22 GTs. and 24 GT have a payback period of < 3 years. This is because a larger ship has a carrying capacity or more carrying capacity. Hand line fishing with a vessel size > 30 GT has a relatively long payback period, i.e. < 5 years. While ships with a size of 5 GT. 6 GTs. 9 GTs. 22 GTs. and 24 GT have a payback period of < 3 years. This is because a larger ship has a carrying capacity or more carrying capacity. Hand line fishing with a vessel size > 30 GT has a relatively long payback period, i.e. < 5 years. While ships with a size of 5 GT. 6 GTs. 9 GTs. 22 GTs. and 24 GT have a payback period of < 3 years.